Proposition D’Une Nouvelle Approche D’Evaluation De L’accès A L’eau: Application Dans La Commune De Savalou (Bénin) - Vifan Eric, Sebo; Sèvègni Brice, Tchahou; Patricia, Assogba; K. Euloge, Agbossou (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
Access to clean water is a topic addressed by many studies worldwide including in Benin, where this issue has been regularly addressed in the angles of the supply and quality modes. Moreover, the official indicators for assessing the access to water as the needs of coverage in water sources or the water service rates do not include aspects of availability of the resource, accessibility and financial ability of households to cope with the water disposal costs at certain water sources. Therefore, the acuteness of the problems related to access is often not noticeable. This study conducted in the municipality of Savalou, so the issue further analysis through the above- mentioned parameters and offers access to potable water index (APEI) aggregating said parameters. To pass the study, a sample of 141 households was used to collect information from households. For the rest, as has been mentioned above, access to drinking water index (APEI) was constructed and compared to the rate of service which is the official indicator of access to clean water. The results reveal deep problems of water availability in terms of poor distribution of water points and population service : outside the hydrogeological characteristics that affect the achievement of water points and limit the flow rates,difficulties related to access water are also noticeable in terms of accessibility : 33.33 % of households travel more than 1000 m in return and 28.36 % of household roam between 400 m and 1000 m in return, to provide drinking water, all seasons. But the WHO standards require that a household should not be more than 200 m in return for supplies of drinking water. The economic value of the water in turn, of 1390 FCFA 41,700 to FCFA to stock between 1 m3 and 30 m3 for a population already quite poor (86.32 % of the population earns less than 50,000 FCFA per month). All this by determining APEI shows that access to water in the Municipality of Savalou is 68.09 % difficult.